ANALISIS PENOKOHAN DALAM NOVEL KARYA ASMA NADIA ANALYSIS OF CHARACTERISTICS IN ASMA NADIA'S NOVEL - Nuraida Anggraeni (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
Novel is one of the most popular types of prose by every literary enthusiast. This is in accordance with the content of the novel which contains the expression of feelings conveyed through a word in the form of prose. This study aims to determine the characterizations contained in the Novel Cinta di Ujung Sajadah. In conducting the analysis, the researcher used a qualitative descriptive method by describing the characterizations contained in the Cinta di Ujung Sajadah novel so that the data found were based on qualitative descriptive methods. In the characterization analysis, the researcher describes the characterizations of the novel Cinta di Ujung Sajadah which include the characterizations of the main character and additional characters. Based on the results of the analysis that has been done, the novel Cinta di Ujung Sajadah has one main character named Cinta and nine additional characters namely Adji, Aisyah, Anggun, Cantik, Makky, Mama Alia, Mbok Nah, Neta, and Papa Cinta.